MitraClip® procedure as bridge to left ventricular assist device: Enable extracorporeal membrane oxygenation weaning and reduce perioperative risk. (April 2023) - Schmiady, Martin O.; Winnik, Stephan; Bettex, Dominique; Aser, Raed
Secondary mitral valve regurgitation is a frequent consequence of left ventricular dysfunction in patients with severe heart failure. The management of this disease can be challenging since it often culminates in refractory pulmonary edema and multi-organ failure. We present the case of a 50-year-old male who was admitted in cardiogenic shock following myocardial infarction. After successful revascularization, percutaneous mitral valve repair using the MitraClip ® device enabled weaning from extracorporeal membrane oxygenation followed by the implantation of a left ventricular assist device as bridge to transplant.